Banks Incentives for Risk-Taking; Evidence of Selected Commercial Banks in Ghana - Razak, Abubakari (Asian Journal of Economic Modelling, 2018)
This paper aims at investigating commercial banks in Ghana incentives for risk taking. It tested the relationship between a selected banks listed on the Ghana stock exchange proxy for risk taking, their Tobin’s q, and factors that influence their desire for risk. The factors that influence banks’ desire for risk taking were derived from a decomposition of the Tobin’s q. and the results of the test reveal that, bank regulations, monetary policies, efficiency, and the banks size significantly influence the banks incentives to risk taking and competition, positively influenced their desire for risk whereas increases in economic growth reduces the banks incentives for risk taking.